2005
DOI: 10.1002/jmv.20466
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein upregulates survivin expression in hepatoma tissues

Abstract: The hepatitis B virus X protein (HBx) plays an important role in the development of hepatocellular carcinoma (HCC). The relationship was examined between HBV antigens and IAP (inhibitor of apoptosis) family in development of HCC. The expression levels of HBV antigens (HBsAg, HBcAg, and HBxAg) and members of the IAP family (survivin, XIAP, cIAP-1, and cIAP-2) were detected immunohistochemically in tissues from 34 cases of HCC and 30 cases of liver cirrhosis. The positive rate of survivin was higher than these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 27 publications
1
88
0
2
Order By: Relevance
“…Previously, we demonstrated that HBx upregulated both the expression and the activity of hTERT in hepatoma [8] . We also found that HBx was able to upregulate the expression of survivin, which suggests that survivin may be involved in the carcinogenesis of HCC that is mediated by HBx [9] . cDNA microarray is a powerful tool for identifying disease-related gene expression profiles in biological samples.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…Previously, we demonstrated that HBx upregulated both the expression and the activity of hTERT in hepatoma [8] . We also found that HBx was able to upregulate the expression of survivin, which suggests that survivin may be involved in the carcinogenesis of HCC that is mediated by HBx [9] . cDNA microarray is a powerful tool for identifying disease-related gene expression profiles in biological samples.…”
Section: Introductionmentioning
confidence: 54%
“…Cell culture The human liver L-O2 cell line (purchased from Nanjing KeyGen Biotech Co Ltd, Nanjing, China), which originated histologically from normal human liver tissue that had been immortalized by stable transfection of the hTERT gene, was used previously [9,[11][12][13] . L-O2-P (cell line from L-O2 cells stably transfected with empty pcDNA3 plasmid) and L-O2-X (cell line from L-O2 cells stably transfected with the HBx gene) were established as described previously [13] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…RNA interference pSilencer-HBx (pSi-HBx) was used to produce small interfering RNAs (siRNAs) to target HBx mRNA, and pSilencercontrol (pSi-con) was used as a negative control [27,28] . siRNA duplexes targeting human MEKK2 were synthesized and purified by RiboBio (Guangzhou, China) [29] .…”
Section: Cell Culturementioning
confidence: 99%